Efeito da Abarema cochliacarpos (Gomes) na lesão muscular induzida pelo veneno de Bothrops leucurus - Oliveira, Jeison Saturnino de (2014)
The snakebite is a public health problem worldwide, especially in tropical countries. The objective of this study was to investigate the mechanisms involved in the effect of hydroethanolic extract of the stem bark Abarema cochliacarpos (EAc) in muscle injury induced by Bothrops leucurus. Male swiss mice were used (28-32g ; n= 6 groups), where they received perimuscular injection Bothrops leucurus venom (BlV 1 mg/Kg/paw Volume 50 ìl) the right hind limb, treated orally (po), with vehicle (saline) or EAc (100, 200 or 400 mg / kg). In the mechanical hypernociception animals were evaluated in time 2, 4 and 6 hours using digital analgesymeter (von Frey). Edema activity in the animals were evaluated at 15, 30, 60 and 90 minutes, using a digital caliper. Have motor activity was assessed by the rota -rod test and the animals were evaluated at 1, 3 and 7 days. Histological evaluation extensor digitorum longus muscle (EDL) was isolated, removed, fixed, paraffin emblocado (Optical Microscopy) and resin (Electron Microscopy) and cut. Tissues were stained with hematoxylin and eosin and observed under optical and electron microscopy and subsequently photographed. The experimental protocols were approved by the ethical committee for animal research at UFS (CEPA: 61/12). The results were analyzed using followed by Student.s t-test. The treatment orally with EAc (400 mg / kg ) inhibited mechanical hypernociception (2h 5.1 ± 0.76, 5.70 ± 0.65 4h, 6h 5.93 ± 0.49, (p < 0, 05) compared with the BlV venom group (2h 2.08 ± 0.33; 4h 2.28 ± 0.18; 6h 2.52 ± 0.24). The inhibition of edema was also seen in activity with EAc (400 mg / kg) (15 min 15.35 ± 0.27; 30 min 12.63 ± 0.69; 60 min 9.38 ± 0,29 and 90 min 6.83 ± 0.66, p < 0.05) compared with the BlV venom group (15 min 29.7 ± 0.17; 30 min 25.8 ± 0.26; 60 min 20.15 ± 0.24 and 90 min 14.76 ± 0.21). Regarding motor activity, the EAc (400 mg / kg) preserved motor ability (1day 83.22 ± 0.46; 3 days 98.02 ± 0.20 and 7 days 119.24 ± 0.48, p < 0.05) compared to the BlV venom group (1 day 20.03 ± 0.26, 3 days 35.22 ± 0.36 and 7 days 111.21 ± 0.18). Histological analysis showed an protection of muscle injury after administration of EAc (400 mg / kg), maintaining muscle fibers. Our results demonstrated that EAc inhibited the harmful effects of the venom, suggesting that this compound has biotechnological potential in adjuvant treatment of snakebite.